Examples of jurisprudential rules and their applications in the judgments of social media - Al-Omar, Nadira Tariq (Journal of Islamic Sciences, 2023)
The research aims to show the impact of jurisprudential rules on the judgments of social communication, Which shows the importance of these jurisprudential rules as containers that surround many branches and jurisprudential issues, which makes them have flexibility, and the amplitude that allows them to serve as the foundations on which many emerging occurrences are based, including emerging cases of the judgments of social media, and this research has dealt with a study The three most recognized rules that affect the judgments of social communication, which are the rules: the rule: “The principle in things is permissiveness,” the rule: “Matters Are Evaluated Based on Their Purposes,” and the rule: “there Should Be neither Harming nor Reciprocating Harm”.
Keywords: application; jurisprudence rules; social communication; judgment